Effect Of Fiber Composition On Mechanical And Physical Properties Of High Loading Wood Fiber Composites - Ashari, Aminullah (2012)

(untitled)
The mechanical properties of wood polymer composites (WPC) consisting of polypropylene (PP) and mixed sawdust (SD) of meranti shorea spp. dominant and rice husk (RH) filler have been studied. Three different fillers loading of 50 wt. %, 60 wt. % and 70 wt. % were used and the process of compounding and extrusion was carried out using a twin screw extruder. Increase in flexural modulus and tensile modulus are observed while tensile strength, elongation at break, flexural strength and Izod impact strength decrease with increasing filler loading. Water absorption capability increased significantly with the increased of filler loading especially composite with 70 wt. % filler loading. Composites with 50 wt. % of filler found to have an optimum mechanical and physical property, thus being used for further study on the effect of coupling agent. The interfacial bonding between wood filler and PP matrix were studied using maleic anhydride grafted polypropylene (MAPP). Three different loading of MAPP with 1 wt. %, 2 wt. % and 3 wt. % were used in this study. Addition of the MAPP shows some improvement especially tensile strength, tensile modulus and flexural properties. Most of the time, an improvements were observed at 1 wt. % of MAPP, further increment of the MAPP did not show any significant impact on the property tested. SD-PP composites consistently produce an excellence mechanical and physical property to compare with RH-PP composite, better aspect ratio value of SD filler is the main reason for the excellence property. SD-PP composites were used for further study on the impact of difference type of specimens conditioning. Tensile and flexural properties decreased with the exposure to difference extreme conditions. The tensile and flexural properties of the SD-PP composite exposed to xenon-arc light affected most to compare with other exposure. SD-PP composite (without MAPP) experience drop in tensile modulus about 46 % and the drop of mechanical properties is due to the photo-oxidation and chain scission of the polymer molecule. The degradation of specimens after 1000 hours exposure Xenon-arc light was also proven by colour change analysis where it is found that all samples lost most of it original colour